PENGARUH DAUN TURI (Sesbania grandiflora) DAN LAMTORO (Leucaena leucocephala) DALAM RANSUM SAPI BERBASIS INDEKS SINKRONISASI PROTEIN - ENERGI TERHADAP SINTESIS PROTEIN MIKROBA RUMEN - Afduha Nurus Syamsi; Fransisca Maria Suhartati; Wardhana Suryapratama (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2017)
An experiment was aimed to assess the use of the legume leaf as a source of protein feedstuff and levels of synchronization protein-energy (SPE) index in the diet of cattles on ammonia (N-NH3) and microbial protein synthesis (MPS). In vitro techniques was done. The research was used a completely randomized design (CRD), with factorially pattern (2x3), the first factor was the two species of legume (Sesbania leaves and Leucaena leaves) and the second factor was the three level of the SPE index (0.4, 0.5, and 0.6), there were 6 treatment combinations and each was 4 replicates. The results showed that no interaction between legume with SPE index, but each factor was significantly effect (P<0.05) on N-NH3 of rumen fluid and MPS. The research concluded that Leucaena leaf is a legume that is better than Sesbania leaf in terms of their ability toincrease MPS. SPE index is the best in producing MPS at level 0.6. Key words: Legume, synchronization of protein and energy index, ammonia, microbial protein synthesis